An experimental evaluation and comparison of film radiography, computed radiography and real-time digital radiography imaging systems - Chang, Jin Min. (2010)
Fatigue cracks are known to be the cause of many aviation accidents. It is extremely crucial to be able to detect these flaws before it causes any catastrophic accidents. Current practices use film radiography to inspect the aircraft’s inaccessible areas such as the aircraft’s wing spar which is covered by the wing skin panel. Due to advancement in technology, many companies are replacing the matured and well established film radiography with newer radiography imaging systems such as computed radiography and real-time radiography that can save time and manpower. Hence this project is to determine the capability of the newer methods compared to the mature film radiography in terms of their ability to detect flaws, their imaging system sensitivity, sharpness and signal to noise ratio. The student used specimens with real cracks to test the three different radiography imaging system. The three different radiography imaging systems are film radiography, computed radiography and real-time digital radiography. The project has shown that the newer imaging system may not be able to perform better than or even as well as the current film radiography. The project also suggest that all the three radiography imaging systems were not sensitive to extremely tight cracks and micro cracks especially when these features are covered with a skin panel. This may indicate that the current radiography practices may not be good enough to find micro cracks. However this problem can be solved by incorporating the use of a micro focus system which can enhance the imaging system’s capability to detect micro cracks. Although, the film and computed radiography imaging system cannot detect micro cracks, it must be emphasised that they are still able to satisfy the industrial requirements for 2% sensitivity when the specimen are of a certain thickness.